Chemical Analytical Study for Determination of Manganese (II) Using Organic Reagent (HPHMAB) in Aqueous Solution by using Spectrophotometric Method - عـــائـــشــة, رولانــا; مـحـمـد رأفــت مـعـروف (Latakia University Journal -Basic Sciences Series, 2022)
This research was conducted to study the possibility of forming a colored complex between Mn2+ ions and 4-Hydroxy-3-[[(2-hydroxy phenyl) methylene] amino] benzene Sulphonic Acid (HPHMAB) to determine Manganese by using the spectrophotometric method in aqueous solutions. The experimental study indicates that the mentioned reagent reacts with Manganese ions and forms yellow- orange complex with maximum absorbance at λmax = 435 nm in aqueous at pH=10. Based on this, all of the factors that affect the formation process of Mn-HPHMAB complex were studied. Beer-Lambert’s law was obeyed within the range (0.1-7) mg/ℓ. The molar absorptivity, complex constant formation and the detection limit were found to be Ԑ= 2.5 x 10+4 ℓ.moℓ-1.cm-1, βK= 1 x 10+3, 0.0023 mg/ℓ respectively. The stoichiometric composition of complex was CMn:HPHMAB = (1:1). The developed method was examined on Manganese standard solutions (RSD% ≤ 8.81%, recovery > 86%). All the obtained data reveal good accuracy and good reliability of the applied method and confirm the possibility of using the reagent (HPHMAB) to determine Manganese.